ANALISIS PENGARUH PENEMPATAN GPS U-BLOX NEO-6MV2 DALAM MOBIL TERHADAP TINGKAT AKURASI SINYAL GPS - Gusmara, Muhammad Daffa; Djuriatno, Waru; Purnomo, Muhammad Fauzan Edy (Jurnal Mahasiswa TEUB, 2024)
Motor vehicle theft is a prevalent issue in Indonesia, with a significant increase in the number of cases in 2023 compared to 2022. To address this problem, the use of GPS Tracker technology can help reduce stolen vehicle losses. However, the effectiveness and accuracy of the GPS Tracker can be affected by its placement in the vehicle. A study aimed to determine the optimal position for the GPS Tracker installation. The study found that the average distance between the GPS Tracker and the receiver in various positions, such as under the driver's dashboard, under the driver's seat, under the front passenger dashboard, under the middle passenger seat, and under the rear seat, were 10.290 meters, 6.106 meters, 9.634 meters, 5.006 meters, 6.522 meters, and 7.141 meters respectively. Based on the analysis, it was concluded that placing the GPS Tracker under the front passenger seat resulted in the highest level of accuracy for receiving data. Keyword: Vehicle, Global Positioning System (GPS), Accuracy, Position.